Bood and Physiological Variables in Thoroughbred Foals During the first 24 hours of Life - Parraguez, Victor H.; Coloma, Ignacio; Riquelme, Raquel; Lianos, Anibal J.; Escobar, Carolina (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2008)
Blood and physiological variables with clinical importance were studied in newborn Thoroughbred foals. Arterial blood samples were taken from 15 foals at 0, 1, 2, 4, 8, 16 and 24 hours after birth. From this samples, PaO2, PaCO2, pH, hemoglobin concentration, hemoglobin saturation with O2 and hematocrite were measured. Simultaneously, rectal temperature, heart rate and breathing rate were also measured. Rectal temperature increased from 37.5 ± 0.1 ºC (time 0) up to 38.3 ± 0.1 ºC (24 hours). Heart rate was highest 1 hour after birth (139.0 ± 6.5 beats/min) and remained between 90-97 beats/min after 4 hours. Respiratory rate was high at time 0 (57 ± 4.6 breaths/min), with a minimum at 8 hours (38 ± 3.8 breaths/min) and then raised again. PaO2 had a minimum value of 62.8 ± 6.4 mm Hg at time 0, increasing up to 89.1 ± 5.0 mm Hg at 24 hours. PaCO2 had a maximum value of 51.3 ± 1.8 mm Hg at time 0, remaining in 42-43 mm Hg between 2 and 8 hours, increasing subsequently. Blood pH had little variation and was between 7.371 and 7.407. Hemoglobin concentration had the highest value of 15.1 ± 0.8 g/dl at the first hour of life and descended afterwards. Hemoglobin saturation with O2 increased gradually from 96.4 ± 2.9 % at time 0 to 100.8 ± 1.3 % at 24 hours. Hematocrite was between 36.4 and 40.0 % and was statistically different (33.8 ± 1.5 %; p < 0.05) only at 16 hours.